Communicable Diseases of the Developing World (Topics in Medicinal Chemistry,, 2018)
This book reviews the current strategies and challenges for the treatment of bacterial, fungal, parasitic and viral infectious diseases in developing countries. Contributing authors present expert analysis on the transmission, epidemiology, bacteriology, pathogenesis and treatment of Neglected Tropical Bacterial Diseases such as Leprosy, Buruli ulcer, and Trachoma. Particular attention is also given to current antifungal agents, their spectrum of activity, mode of action, limitations, and current challenges in antifungal therapy. The authors explore the medicinal chemistry efforts that gave rise to currently launched drugs and new anti-HIV agents, and they also highlight the latest vaccine and drug developments in the clinical management of the Ebola Virus Disease, ignited by the 2014-2016 outbreak. This work has an interdisciplinary appeal and will engage scholars and professionals in the burden of communicable diseases.